Database on GHG experiments conducted under the LivestockPlus project - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
The database contains data collected from experiments conducted different regions of Colombia (Meta, Atlántico, Casanare and Valle del Cauca). Specifically the data is on GHG emissions from urine and manure patches in grazed pastures and carbon stocks in representative pastures. In addition, there is data on enteric methane production. The collected data can be used as inputs for calculating national GHG emissions factors.